The Cross-Species Immunity During Acute Babesia Co-Infection in Mice - Zafar, Iqra; Galon, Eloiza May; Kondoh, Daisuke; Efstratiou, Artemis; Li, Jixu; Ji, Shengwei; Liu, Mingming; Li, Yongchang; Hasegawa, Yae; Zhou, Jinlin; Xuan, Xuenan (Frontiers in Cellular and Infection Microbiology, 2022)
Babesiosis causes high morbidity and mortality in immunocompromised individuals. An earlier study suggested that lethal Babesia rodhaini infection in murine can be evaded by Babesia microti primary infection via activated macrophage-based immune response during the chronic stage of infection. However, whether the same immune dynamics occur during acute B. microti co-infection is not known. Hence, we used the mouse model to investigate the host immunity during simultaneous acute disease caused by two Babesia species of different pathogenicity. Results showed that B. microti primary infection attenuated parasitemia and conferred immunity in challenge-infected mice as early as day 4 post-primary infection. Likewise, acute Babesia co-infection undermined the splenic immune response, characterized by the significant decrease in splenic B and T cells leading to the reduction in antibody levels and decline in humoral immunity. Interestingly, increased macrophage and natural killer splenic cell populations were observed, depicting their subtle role in the protection. Pro-inflammatory cytokines (i.e. IFN-γ, TNF-α) were downregulated, while the anti-inflammatory cytokine IL-10 was upregulated in mouse sera during the acute phase of Babesia co-infection. Herein, the major cytokines implicated in the lethality caused by B. rodhaini infection were IFN- γ and IL-10. Surprisingly, significant differences in the levels of serum IFN- γ and IL-10 between co-infected survival groups (day 4 and 6 challenge) indicated that even a two-day delay in challenge infection was crucial for the resulting pathology. Additionally, oxidative stress in the form of reactive oxygen species contributed to the severity of pathology during acute babesiosis. Histopathological examination of the spleen showed that the erosion of the marginal zone was more pronounced during B. rodhaini infection, while the loss of cellularity of the marginal zone was less evident during co-infection. Future research warrants investigation of the roles of various immune cell subtypes in the mechanism involved in the protection of Babesia co-infected hosts.